Penegakan Hukum Dalam Pelaksanaan Perjanjian Pengadaan Rumah Antara Developer Dan Konsumen - Icha Anggraini; Nafa Faudilah One Shuc; Fira Rahmanda Sari; Helfira Citra (GLOBAL SCIENTS PUBLISHER, 2024)
Law enforcement in the implementation of a home procurement agreement between developers and consumers is a crucial aspect in maintaining justice and legal certainty for the stability of the property business and consumer trust. This agreement often involves a number of rights and obligations that must be complied with by both parties. The topic discussed in this paper aims to analyze the economic and business aspects in the implementation of a home procurement agreement with a focus on existing law enforcement mechanisms, including laws and regulations governing this transaction, as well as the challenges faced by consumers in claiming their rights. The method used in this paper is a literature study, namely by reading a lot of related regulatory literature and case analysis, which reveals that many consumers have difficulty in enforcing their rights due to a lack of understanding of complex agreements and legal procedures. The results of this paper indicate that it is necessary to increase lagal eduaction for consumers and strengthen regulations to ensure that home procurement agreements can be implemented fairly and transparently. Effective law enforcement not only prtotecs consumer rights, but also increases public trust in the property industry as a whol